ANALISIS MEDIA MONTASE TERHADAP PERKEMBANGAN MOTORIK HALUS ANAK USIA 4-5 TAHUN - Syawalia, Ghina Fairuz Fakhirah; Rahman, Taopik; Giyartini, Rosarina (Universitas Pendidikan Indonesia (UPI), 2021)
Montage media is a tool used in learning in the form of creating new images from several combinations of existing images and then combining them on a new page to make a new, more imaginative work. This montage media is used because it has many benefits for children aged 4-5 years. So that children can develop properly and optimally. This article is entitled